Transcription Factors Associated With IL-15 Cytokine Signaling During NK Cell Development - Wang, Xiang; Zhao, Xiang-Yu (Frontiers in Immunology, 2021)
Natural killer (NK) cells are lymphocytes primarily involved in innate immunity and possess important functional properties in anti-viral and anti-tumor responses; thus, these cells have broad potential for clinical utilization. NK cells originate from hematopoietic stem cells (HSCs) through the following two independent and continuous processes: early commitment from HSCs to IL-15-responsive NK cell progenitors (NKPs) and subsequent differentiation into mature NK cells in response to IL-15. IL-15 is the most important cytokine for NK cell development, is produced by both hematopoietic and nonhematopoietic cells, and functions through a distinct delivery process termed transpresentation. Upon being transpresented to NK cells, IL-15 contributes to NK cell development via the activation of several downstream signaling pathways, including the Ras-MEK-MAPK, JAK-STAT5 and PI3K-ATK-mTOR pathways. Nonetheless, the exact role of IL-15 in NK cell development has not been discussed in a consecutive and comprehensive manner. Here, we review current knowledge about the indispensable role of IL-15 in NK cell development and address which cells produce IL-15 to support NK cell development and when IL-15 exerts its function during multiple developmental stages. Specifically, we highlight how IL-15 supports NK cell development by elucidating the distinct transpresentation of IL-15 to NK cells and revealing the downstream target of IL-15 signaling during NK cell development.